The effects of test item format on self-efficacy and worry during a high-stakes computer-based certification examination. - Mulkey, J. R.; O'Neil, H. F. (Computers in Human Behavior)
Part of a special issue on computer-based performance assessment of problem solving. A study was conducted to examine the effects of test item format on state worry and state self-efficacy as a result of completing a computerized, high-stakes certification examination. The certification test administered used both multiple-choice and open-ended formats. Subjects were 610 male Certified NetWare Engineer™ candidates, who were asked to describe their thoughts and feelings regarding the recently completed certification examination. Findings revealed that there is no significant effect of item format on either state worry or state self-efficacy. However, it was observed that subjects who achieved mastery status in the exam demonstrated both significantly higher levels of state-efficacy and less state worry than did those who failed the exam.